Vectors and Vector-borne diseases in Qatar: epidemiology and key challenges - Devendra Bansal (255958) (2024)
Background Vector-borne diseases (VBDs) account for 17% of the estimated global burden of all infectious diseases and seriously threaten global public health. Human migration, population growth, trade, and climate and environmental changes increase the risk of VBDs’ geographic expansion. Although Qatar does not have indigenous cases of VBDs, the influx of expatriate workers from VBDs endemic countries and the environment and climate being suitable for vector mosquitoes suggest a potential risk for local transmission. We aimed to define the types and distribution of mosquitoes that are of public health concern and the epidemiological features of VBDs in Qatar. Methods VBD cases reported to Qatar’s Ministry of Public Health between 2013 and 2021 were analyzed with descriptive statistics. Field surveys were conducted between 2021 and 2022, and mosquitoes were collected using a variety of traps from 8 different municipalities in Qatar. Collected samples were subjected to morphological followed by molecular characterization. Results A total of 4,092 and 166 cases of malaria and dengue fever were respectively reported during the study period. The mean incidence of malaria and dengue was estimated to be 13.5/100,000 and 0.7/100,000 population, respectively. The majority of the VBD cases were male, non-Qatari, between 20-50 years of age (matching Qatar’s overall population demography), and notified during the hot months (June-September). The results of the adult mosquito trappings showed that Culex quinquefasciatus is the most widespread followed by Cx. Pipiens, Aedes caspius, Anopheles stephensi Cx. tritnaneorhynchus, Cx. sitiens, Culiseta longiareolata, Cx. thileri, and Ochlerotatus caspius voucher. Conclusion This study has provided crucial information regarding the presence and various types of vectors and VBDs in Qatar. It highlights the need for further research and prevention strategies. Enhanced surveillance is necessary to assess the distribution and biting habits of vectors and to prevent local transmission by identifying and isolating imported cases.